Documentation of the export restrictions and import tariffs overall impacts (ERATO) PE model - Estrades, Carmen; Gao, Yuan; Laborde Debucquet, David (International Food Policy Research Institute, 2012)
Partial equilibrium (PE) analysis is commonly used to analyze the effects of policies, in particular trade policies, on price and welfare in the market that is directly affected. The partial equilibrium model only depicts the economy in one particular sector or market. In the case of a single commodity PE, this approach neglects the indirect effects through which changes in the demand or supply for one good may influence the market for another good. Different from many single-commodity partial equilibrium models, the Export Restrictions And import Tariffs Overall impacts (ERATO) 1model illustrates how a multi-market model can be used to analyze trade policy options in a context of a multi-product value chain.